Cell-based Therapy for Hypertension: Challenges and Perspectives - Junior, Arquimedes G.; dos Reis L, Francislaine Aparecida (Current Pharmaceutical Design, 2018)
Hypertension is a non-transmissible chronic disease with a high prevalence, morbidity, and mortality. Different strategies for the treatment of hypertension are employed worldwide, but the control of hypertension remains a major challenge for global health. Many unsuccessful unconventional therapies have been proposed in recent years, including herbal medicines and the development of small molecules or antibodies that seek to disrupt the disease's pathogenesis. Cell-based therapies may be used as replacement or complementary treatment strategies. The results of recent preclinical studies of cell-based therapies are promising. However, human clinical trials are scarce, the data are insipid, and many issues have been raised about the safety and efficacy of cell-based therapies. The present review summarizes research on cell-based therapy for hypertension. We also briefly summarize relevant clinical trials and discuss future perspectives and possible clinical applications.
Keywords: antibodies